Coseismic Slip Vectors of 24 August and 30 October 2016 Earthquakes in Central Italy: Oblique Slip and Regional Kinematic Implications. Issue 10 (18th October 2018) - Perouse, Eugénie; Benedetti, Lucilla; Fleury, Jules; Rizza, Magali; Puliti, Irene; Billant, Jeremy; Van der Woerd, Jerome; Feuillet, Nathalie; Jacques, Eric; Pace, Bruno
Abstract: After 24 August and 30 October 2016 central Italy earthquakes (Mw 6.0 and 6.5, respectively), photogrammetry and geodetic survey were performed at various sites along a 6‐km‐long portion of the rupturing Monte Vettore fault system, providing very high‐resolution georeferenced 3‐D point clouds and imagery of the 24 August rupture and a data set of bedrock fault scarp before/after the 30 October earthquake. The maximum coseismic displacement for both events occurs near Scoglio dell' Aquila with an average normal dip slip of 22 ± 4 and 184 ± 6 cm, respectively. Coseismic slip vectors and meter‐scale corrugation axis are oriented N280 ± 10° on the ~N140° striking main Vettore fault involving oblique normal slip with a right‐lateral component and N205 ± 10° on ~N170° fault strands implying oblique normal slip with a left‐lateral component. We quantify the near‐field coseismic displacements of the Monte Vettore fault for the 30 October event: the footwall has been translated horizontally by 42 ± 2 cm toward the ENE and uplifted by 11 ± 2 cm. The hangingwall has moved horizontally by 26 ± 2 cm, toward the NW, in a direction parallel to the fault plane and subsided by 116 ± 2 cm. The fault geometry and our determined surface coseismic slip vectors are mechanically compatible with a σ3 = N65 ± 15°. This stress regime is consistent with the 30 October 2016 focal mechanism and the relative motion between the Adriatic microplate and the Tyrrhenian coastal region. The 30 October surface rupture results from seismic slip at depth and thus has a tectonic origin. Plain Language Summary: After 24 August and 30 October 2016 central Italy earthquakes, we acquire a very high‐resolution data set of the effect of the fault at the surface before and after the 30 October earthquake. Those data sets allow quantifying the motion of each compartment on both side of the fault during the earthquake and the direction of this motion. The footwall has been translated horizontally by 42 ± 2 cm toward the ENE and uplifted by 11 ± 2 cm. The hangingwall has moved horizontally by 26 ± 2 cm, toward the NW, and subsided by 116 ± 2 cm. These results are consistent with the seismic data and suggest that surface ruptures observed are resulting from seismic slip at depth. Key Points: We provide unique data set of high‐resolution georeferenced 3‐D point clouds of bedrock fault scarp before and after the 30 October earthquake The near‐field coseismic displacements of the Monte Vettore fault for the 30 October is quantified The 30 October surface rupture results from seismic slip at depth and has thus a tectonic origin